Tramas de una investigación: inferencias abductivas y analógicas en un caso freudiano - Elodia Elisabeth Granados; Alejandra Gabriele; Liliana Sánchez Mendiburo; Mariela Soledad Trujillo.; María Mercedes Cabaña (Perspectivas Metodológicas​)
In the present investigation we analyze the methodological procedures of psychoanalysis research, from exploring inferential operations in the Freudian clinical case "From the History of a Child Neurosis (1914-18)". The identification of different logical procedures led to the need to carry out theoretical extensions and identify two units of analysis: on the one hand the dream and the primordial scene, illustrative of the procedures present in the analytic experience; and on the other, anal erotism and castration complex, which allowed us to identify inferences of the theoretical argumentation. At the moments of analysis, analogical and abductive inferences were clearly identified. When Freud orders the elements arising in the analysis and constructs theory, it produces a series of chains of analogical / abductive inferences that characterize a Freudian inferential procedure. This allows us to acknowledge psychoanalysis as a type of knowledge that has its own logical-methodological way of proceeding based on the uniqueness of the experience.